Adipocyte lipid storage and adipokine production are modulated by lipoxygenase-derived oxylipins generated from 18-carbon fatty acids. (July 2017) - Zahradka, Peter; Neumann, Shannon; Aukema, Harold M.; Taylor, Carla G.
Highlights: Oxylipins generated from short-chain PUFAs block lipid accumulation by adipocytes. The oxylipins operate by modulating the levels of key proteins involved in lipid metabolism. The effects of oxylipins on protein levels are not due to changes in gene expression. Abstract: Generation of oxylipins (oxygenated metabolites of fatty acids) by lipoxygenases may be responsible for the beneficial effects of 20- and 22-carbon n-3 fatty acids on adipose tissue dysfunction in obesity, but the potential actions of oxylipins derived from 18-carbon fatty acids, which are generally at higher levels in the diet, are unknown. We therefore compared the effects of select lipoxygenase-derived oxylipins produced from α-linolenic acid (ALA, C18:3 n-3), linoleic acid (LA, C18:2 n-6), and arachidonic acid (AA, C20:4 n-6) on key adipocyte functions that are altered in obesity. Individual oxylipins were added to the culture medium of differentiating 3T3-L1 preadipocytes for 6 days. Lipid accumulation was subsequently determined by Oil Red O staining, while Western blotting was used to measure levels of proteins associated with lipid metabolism and characteristics of adipocyte functionality. Addition of all oxylipins at 30 nM was sufficient to significantly decrease triglyceride accumulation in lipid droplets, and higher levels completely blocked lipid production. Our results establish that lipoxygenase-derived oxylipins produced from 18-carbon PUFA differentially affect multiple adipocyte processes associated with lipid storage and adipokine production. However, these effects are not due to the oxylipins blocking adipocyte maturation and thus globally suppressing all adipocyte characteristics. Furthermore, these oxylipin species decrease the lipid content of adipocytes regardless from which precursor fatty acid or lipoxygenase they were derived. Consequently, adipocyte characteristics can be altered through the ability of oxylipins to selectively modulate levels of proteins involved in both lipid metabolism and adipokine production.